Meningkatkan Kemampuan Menyimak Melalui Metode Bercerita pada Anak Kelompok A di TK Siti Khodijah Pucuk Lamongan - Suhartini Nurul Azminah (PG-PAUD Trunojoyo, 2018)
Listening has a fundamental function of life including the preschoolers. Human use more time of listening activities for about 50%, while the rest 50% are used for speaking, reading, and writing. Listening activities should begin early for children in all situations. But,it is not in line with the listening ability of group A children in Kindergarten SitiKhodijahPucukLamongan. They have some difficulties when being asked by the teacher to listen to information given. Listening is a tedious activity for children, especially preschoolers. It is necessary to have similar material and interesting way to practice listening skills in preschoolers.According to the problem, the research questions are formulated as follows (1) How the application of storytelling method to improve the listening ability of children group A in Kindergarten SitiKhodijahPucukLamongan?, (2) How to improve the listening ability through the storytelling method of group Achildren in Kindergarten SitiKhodijahPucukLamongan? The purpose of this study are (1) To find out how the application of storytelling method to improve the listening ability in children group A in Kindergarten SitiKhodijahPucukLamongan, (2) To know the improvement of listening ability through storytelling method of group A in Kindergarten SitiKhodijahPucukLamongan.This study uses a Classroom Action Research in which there are actions of teachers in two cycles. On the first cyclethe percentage of children who are able based on criteria of Exponential Developing Criteria (BSH) reaches 33.33% while in the second cyclethe percentage of children who are able increases to 83.33%. Based on the result of this study, it can be concluded that the method of storytelling can improve the listening ability of children group A in Kindergarten SitiKhodijahPucukLamongan.